Leukocyte extracellular vesicles as the first biomarkers to predict outcomes in patients undergoing percutaneous aortic valve replacement. (3rd October 2022) - Gasecka, A; Van Der Pol, E; Kochman, J; Huczek, Z; Wilimski, R; Grabowski, M; Filipiak, K J; Nieuwland, R
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is a novel treatment for aortic stenosis (AS), associated with better outcomes than surgical aortic valve replacement in high-risk patients. However, up to 29% of patients annually experience major adverse cardiac and cerebrovascular events (MACCE) after TAVI. MACCE are mostly caused by atherothrombosis, i.e. formation of platelet aggregates (thrombi) on ruptured atherosclerotic plaques. Because platelets release extracellular vesicles (EVs) during thrombus formation, we hypothesized that EVs are a biomarker to predict MACCE after TAVI. Methods: This was a multicentre, prospective clinical study. Venous blood was collected 1 day before TAVI and at hospital discharge (n=57, mean age 79.9+6.4 years, 49% male). Flow cytometry (Apogee A60-Micro) was used to determine concentrations of plasma EVs labelled with markers for endothelial cells (CD146), leukocytes (CD45), platelets and megakaryocytes (CD61) and activated platelets (CD62p). Analysis of flow cytometry data files was fully automated. Rosetta Calibration (Exometry) and Flow-SR were used for diameter and refractive index determination. Wilcoxon signed rank test was used to compare EV concentrations before and after TAVI. The predictive value of EVs for MACCE and the cut-offs were calculated using a receiver operating characteristic curve. Logistic regression model incorporating EV concentrations and clinical characteristics was used to determine the best model for MACCE prediction. Results: Concentrations of EVs from activated platelets increased, whereas from leukocytes decreased after TAVI, compared to the measurement before (p=0.06, p=0.04, respectively). Among 55 patients discharged from the hospital, 14 patients experienced MACCE (25%) during the median 15 months of observation. Increased baseline concentration of leukocyte EVs and male gender were the only independent predictors of MACCE in multivariable analysis (OR 4.01, 95% CI 0.77–23.77, p=0.04 for leukocyte EVs; OR 6.84, 95% CI 1.41–33.17, p=0.03 for male gender). Conclusions: We identified increased concentrations of leukocyte EVs as new candidate biomarkers to predict MACCE after TAVI. Leukocyte EVs could be used to augment risk stratification in this patient cohort. The next step is to validate the clinical applicability of EVs to predict post-TAVI MACCE in a large-scale clinical trial. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Young Investigator Grant of the Polish Society of Cardiology